The use of simulation technologies to optimize the processes of transportation of crop production - Nekrasov S.I.; Apatenko A.S. (BIO Web of Conferences)
Methodological approaches to the substantiation of groups of optimization criteria for mathematical modeling of planning and distribution structures are considered in detail. To justify methodological approaches for optimizing the transportation process, it is necessary to take into account not only transportation conditions, but also indicators of the trouble-free operation of vehicles. It has been established that cost-effective characteristics of transport and technological processes have been studied and determined using mathematical analysis. Based on this model, recommendations have been presented for optimizing transportation processes. The model can be used to study and predict the development of freight transportation systems in the agricultural sector.